Accuracy of Markerless 3D Motion Capture Evaluation to Differentiate between On/Off Status in Parkinson’s Disease after Deep Brain Stimulation - Hector R. Martinez; Alexis Garcia-Sarreon; Carlos Camara-Lemarroy; Fortino Salazar; María L. Guerrero-González (Parkinson's Disease)
Background. Body motion evaluation (BME) by markerless systems is increasingly being considered as an alternative to traditional marker-based technology because they are faster, simpler, and less expensive. They are increasingly used in clinical settings in patients with movement disorders; however, the wide variety of systems available makes results conflicting. Research Question. The objective of this study was to determine whether a markerless 3D motion capture system is a useful instrument to objectively differentiate between PD patients with DBS in On and Off states and controls and its correlation with the evaluation by means of MDS-UPDRS. Methods. Six PD patients who underwent deep brain stimulation (DBS) bilaterally in the subthalamic nucleus were evaluated using BME and the Unified Parkinson’s Disease Rating Scale (UPDRS-III) with DBS turned On and Off. BME of 16 different movements in six controls paired by age and sex was compared with that in PD patients with DBS in On and Off states. Results. A better performance in the BME was correlated with a lower UPDRS-III score. There was no statistically significant difference between patients in Off and On states of DBS regarding BME. However, some items such as left shoulder flexion (p=0.038), right shoulder rotation (p=0.011), and left trunk rotation (p=0.023) were different between Off patients and healthy controls. Significance. Kinematic data obtained with this markerless system could contribute to discriminate between PD patients and healthy controls. This emerging technology may help to clinically evaluate PD patients more objectively.